Nursing Technicians: The Unsung Heroes in Patient Care and Hospital Operations - Zahra Hussine Eisa Alhazmi, Amal Ahmad Ali Sabai, Sarah Nasser Hussin Altherwi, Tagiah Mohammad Hassan Altherwi, Azizah Nasser Hussine Altherwi (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Nursing technicians are indispensable members of the healthcare team, providing vital support in patient care across various settings. From hospitals to nursing homes, they assist with tasks like taking vital signs, aiding in daily activities, and communicating patient needs. Research shows their presence correlates with better patient outcomes. However, nursing technicians face challenges such as understaffing, low wages, and lack of recognition. Strategies to address these issues include advocating for safe staffing ratios, standardized education, higher compensation, and career advancement opportunities. Elevating their role is crucial for enhancing healthcare quality and alleviating workforce shortages. By recognizing their contributions and investing in their professional growth, healthcare organizations can empower nursing technicians to continue their essential work in ensuring quality patient care and smooth hospital operations.